Borderline Disorder: (De Facto) Historical Ethnic Borders and Contemporary Conflict in Africa - Emilio Depetris-Chauvin; Ömer Özak (Institute of Labor Economics (IZA), 2020)
We explore the effect of historical ethnic borders on contemporary conflict in Africa. We document that both the intensive and extensive margins of contemporary conflict are higher close to historical ethnic borders. Exploiting variations across artificial regions within an ethnicity's historical homeland and a theory-based instrumental variable approach, we find that regions crossed by historical ethnic borders have 27 percentage points higher probability of conflict and 7.9 percentage points higher probability of being the initial location of a conflict. We uncover several key underlying mechanisms: competition for agricultural land, population pressure, cultural similarity and weak property rights.
Keywords: D74; N57; O13; O17; O43; P48; Q15; Q34; 330; borders; conflict; territory; property rights; landownership; population pressure; migration; historical homelands; development; Africa; Voronoi tessellation; Thiessen tessellation